Horizontal Cleavage Meniscus Tear: “The Quad Tendon Augmentation Technique” - Maximiliano Ibañez, M.D.; Felix Hoffmann, M.D.; Caroline Mouton, Ph.D.; Romain Seil, M.D., Ph.D. (Arthroscopy Techniques, 2024)
The management of medial meniscus horizontal cleavage tears can be challenging. Currently, several treatment options, including nonoperative and surgical options, have been proposed in the literature. Different repair techniques aiming to promote the healing process have been reported and have shown good outcomes. However, recurrent parameniscal cysts and decreased meniscal volume have also been reported. In this Technical Note, a novel surgical technique to repair a horizontal cleavage tear of the posterior horn of the medial meniscus is reported in young patients. The technique uses a strip of autologous quadriceps tendon to fill the void between the upper and lower meniscal leaflets followed by an all-inside compression suture. Both of these technical features aim to overcome the limitations of current repair techniques.